PENGARUH KEADILAN PROSEDURAL DAN PROSES REKRUTMEN TERHADAP KINERJA KARYAWAN BAKSO BAKAR AMBYAR - Santoso, Calvin Denny; Raharjo, Itot Bian (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This research was conducted with the aim of knowing the effect of two variables, namely procedural justice, the recruitment process and employee performance at UMKM Bakso Bakar Ambyar Ngadiluwih. The method used in this study is a quantitative research method with sampling techniques using saturated samples, namely with a total sample of 35 respondents which are all employees at Bakso Bakar Ambyar. Data collection in this study included observations, questionnaires, and literature studies where the results of data collection were tested using the SPSS version 25 application through validity testing, reliability testing, classical assumption testing, Kolmogorov testing, normality testing, multiple linear regression analysis, and testing. hypothesis. The results of the research tests that have been carried out conclude that the Procedural Justice variable is obtained by t count > t table, namely 5.678 > 1.684 and the variable obtained by Recruitment Proces obtained by t count > t table, namely 3.415 > 1.684. This shows that the variables of procedural justice, the recruitment process and have a positive and significant effect on employee performance.